Change from baseline as an outcome illustrates escape behaviour of rats in hot plate method - Pathapati, Rama Mohan; Rajesh Kumar, Manchi; Kudagi, B. L.; Buchineni, Madhavulu (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The Hot Plate test is a thermal hyperalgesia model to assess the analgesic activity of many compounds. Traditional analysis compares reaction times with controls, reports only analgesic activity without considering escape reflex. Escape reflex to pain sensation also provides an indirect measure of analgesic activity. However, it requires repeated exposure of rats to hot plate. We explored the learning activities and escape behaviour of rats by calculating the change from baseline of reaction times. Methods: Male Wister strain albino rats, weighing between 150-200mg were used for assessment of hot-plate induced hyperalgesia. Author analysed the analgesic activity of aspirin (100mg/Kg) and compared with animals receiving saline. Aspirin and saline were administered 1hr orally before the commencement of the experiment. The reaction time was recorded at every 30 min up to 6hrs. Results: With traditional analysis, we can observe that the onset of action, peak action and duration of analgesic activity of aspirin was at 0.5, 2.0 and 5.0 hours respectively. Peak inhibition of reaction time was seen at 2 hours with a magnitude of 474%. When we applied a statistical procedure, absolute change from baseline statistics, we found that animals treated with aspirin also exhibited escape reflex after fading of drug response and animals treated with saline demonstrated early (0.5hr) escape behaviour from the hot plate and continued throughout the rest of the experiment. Conclusions: Change from baseline as an outcome illustrates escape behaviour of rats in hot plate method and it should be employed along with percentage inhibition during assessment of analgesic activity.